2022
DOI: 10.3389/fimmu.2022.988667
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine labelling of therapeutic human tolerogenic dendritic cells for 19F-magnetic resonance imaging

Abstract: Tolerogenic dendritic cell (tolDC) therapies aim to restore self-tolerance in patients suffering from autoimmune diseases. Phase 1 clinical trials with tolDC have shown the feasibility and safety of this approach, but have also highlighted a lack of understanding of their distribution in vivo. Fluorine-19 magnetic resonance imaging (19F-MRI) promises an attractive cell tracking method because it allows for detection of 19F-labelled cells in a non-invasive and longitudinal manner. Here, we tested the suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This is the first in vivo MPI study that employed multichannel joint image reconstruction with a focused FOV for image acquisition and represents an important step forward in establishing MPI as a non-invasive imaging modality capable of tracking the fate of injected DC to serve as a surrogate marker of therapeutic effectiveness. Recently, DC-based therapies have garnered much interest within combination cancer immunotherapy in autoimmune and transplantation settings [58] as well as in infectious disease settings such as SARS-CoV-2 [59]. Regardless of disease setting, non-invasive and quantifiable imaging is required for cell-based immunotherapies to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first in vivo MPI study that employed multichannel joint image reconstruction with a focused FOV for image acquisition and represents an important step forward in establishing MPI as a non-invasive imaging modality capable of tracking the fate of injected DC to serve as a surrogate marker of therapeutic effectiveness. Recently, DC-based therapies have garnered much interest within combination cancer immunotherapy in autoimmune and transplantation settings [58] as well as in infectious disease settings such as SARS-CoV-2 [59]. Regardless of disease setting, non-invasive and quantifiable imaging is required for cell-based immunotherapies to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this is the first in vivo MPI study that employed multichannel joint image reconstruction with a focused FOV for image acquisition and represents an important step forward in establishing MPI as a noninvasive imaging modality capable of tracking the fate of injected DC to serve as a surrogate marker of therapeutic effectiveness. Recently, DC-based therapies have garnered much interest within combination cancer immunotherapy in autoimmune and transplantation settings [ 59 ] as well as in infectious disease settings such as SARS-CoV-2 [ 60 ]. Regardless of disease setting, noninvasive and quantifiable imaging is required for cell-based immunotherapies to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to mature moDCs, tolDCs generated with Dexa and the active form of VitD3 have substantially reduced expression of CCR7 and therefore a limited capacity to migrate in a CCR7-dependent manner [ 53 ]. Indeed, these tolDCs failed to migrate towards the draining lymph node after administration into an inflamed knee joint of a RA patient, as determined by imaging of 111 Indium-labelled tolDCs [ 54 ] This observation possibly explains the local but not systemic effects of tolDC administration [ 39 ]. It is therefore crucial to improve our understanding of the biodistribution of tolDCs after administration via different routes and how this relates to their immunomodulatory actions.…”
Section: In Vivo Tracking Of Therapeutic Toldcsmentioning
confidence: 99%
“…In the tolDC field, we (Hilkens and colleagues) have recently tested the labelling of therapeutic human tolDCs with nanoparticles containing 19 F ( 19 F-NP) for detection by 19 F-MRI [ 54 ]. We found that tolDCs readily endocytosed 19 F-NP with acceptable effects on cell viability and yield and, importantly, without affecting the tolerogenic features of the cells.…”
Section: In Vivo Tracking Of Therapeutic Toldcsmentioning
confidence: 99%